DEL DERECHO ROMANO A LAS TRADICIONES JURÍDICAS - Escobar Córdoba, Federico (2023)
The authorís thesis is that the degree of attention Roman law receives in civilian law schools is excessive, in light of the wider understanding of the law that befits a multicultural world. The text begins by exploring globalization, emphasizing the cultural processes that have molded contemporary societies. The article then offers a sample of the kind of praise frequently received by Roman law, and turns to a cultural critique that exposes some of its deficiencies, as well as the way in which essential contributions made by other cultures have been silenced. The author proceeds by showing the persistence of Roman law in universities, and its precarious situation today. The document concludes with a brief presentation of the notion of legal traditions, and suggests some ways in which turning to this method may enrich the study of law.